Prison song - Martin, Darnell; Q-Tip; Blige, Mary J; Perrineau, Harold; Snow ([Los Angeles, CA] : New Line Home Entertainment, 2003)
"Hip Hop and R & B sensations Q-Tip and Mary J. Blige star in this gripping drama of a young man's fight against an unfair justice system and his struggle to escape life in the ghetto. ... Prison Song is an emotional and unforgettable story of courage and hope on the streets of New York"--Container.
Title from opening frames.
Special features: widescreen and fullscreen versions of the film; trailers; DVD-ROM content.
Closed-captioned.
DVD ; Region 1 ; Dolby digital 5.1 surround sound, stereo. surround sound.; System requirements for DVD-ROM and online features: Microsoft Windows 98SE or higher, InterActual Player (included), Microsoft Internet Explorer 5.0 or higher, an Internet connection, a DVD-ROM drive, and a software or hardware DVD player. This DVD will not work in a CD-ROM drive and the DVD-ROM features are not available on Apple Macintosh.
Keywords: New York, N.Y. -- Drama; Inner cities -- New York State -- New York -- Drama; Inner cities